Structural Aspects of Railway Truss Bridges Affecting Transverse Shear Forces in Steel-Concrete Composite Decks - Siekierski Wojciech (Civil and Environmental Engineering Reports, 2015)
At the steel-concrete interface, the horizontal shear forces that are transverse to cross beams occur due to joint action of the steel-concrete composite deck and the truss girders. Numerical analysis showed that values of the forces are big in comparison to the longitudinal shear forces. In both cases extreme force values occur near side edges of a slab. The paper studies possibilities of reduction of these shear forces by structural alterations of the following: rigidity of a concrete slab, arrangement of a wind bracing, arrangement of concrete slab expansion joints. An existing railway truss bridge span has been analysed. Numerical analysis shows that it is possible to reduce the values of shear forces transverse to cross beams. It may reach 20% near the side edges of slabs and 23% in the centre of slab width.